Annatto in diets Carassius auratus goldfish fingerlings: growth performance and skin pigmentation - Fries, Edionei Maico; Bittarello, Alis Correia; Zaminhan, Micheli; Signor, Altevir; Feiden, Aldi; Boscolo, Wilson Rogério (Semina: Ciências Agrárias, 2014)
This study evaluated the effect of adding annatto as agent pigmentation on the staining characteristics of the skin, muscle and productive performance of Carassius auratus, reared in 0.15 m3 (dimensions 0.50 x 0.50 x 0.65 m) hapas disposed within a circular masonry tank of 25 m3. We used 336 C. auratus fingerlings completely randomized design in 28 hapas with seven treatments and four replicates with 12 fish per unit. The addition of annatto levels were 0.0, 0.25, 0.50, 1.00, 2.00, 4.00 and 8.00%. Fish with an average initial weight of 1.12 Â± 0.18 g and length of 4.31 Â± 0.44 cm, were fed the 08, 11, 14 and 17 hours. The b * colorimetric characteristics (yellow) showed significant at 96 and 141 days in the Hunter coordinate system with the addition of 2.0 and 1.0% annatto in the diet, respectively, and the coordinate system of CMYK and 96 days for C (cyan), and 141 days for the Y (yellow), with the addition of 8.0 to 2.0% annatto in the diet, respectively. We observed differences (P <0.05) average final weight, weight gain, feed conversion, daily growth rate and feed efficiency. It is recommended a diet containing 1.0% added annatto to C. auratus to better performance and 1.0 to 4.0% added annatto to intensified light fish skin.